Pengaruh Religiusitas dan Tingkat Pendidikan terhadap Persepsi Mahasiswa Akuntansi terkait Penggelapan Pajak - Hidayah, Yani Balqis; Cheisviyanny, Charoline (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to analyze the effect of religiosity and educational level on accounting students' perceptions of tax evasion. the sample was determined by the slovin formula. the type of data is primary data using multiple regression analysis. the findings provide evidence that religiosity and educational level have an effect on students' perceptions of tax evasion. the study provides important insights into designing more effective tax education programs that take into account religious values in higher education. This study provides important insights for designing more effective tax education programs that take into account religious values in higher education.